Zasada równego dostępu do środków budżetowych jednostek samorządu terytorialnego dla wykonawców zadań publicznych - Szumlakowski, Roman (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The limit of the principle of equal access to local government budget for contractors providing public services has been clearly laid out in Article 32 of the Constitution of the Republic of Poland in relation to Article 7 of the Act of 29 January 2004 — Public Procurement Law. The principle of equal access to the local government budget for contractors providing public services is not absolute, as it requires equal treatment for operators applying for the award of a public contract in a similar factual situation, and performing a similar activity to each other only in the public tender. It is important that the nature of the anti-discrimination principle of equal access to the budget of local government units is closely correlated with the principle of maintaining fair competition, which complements the above legal principle. Its main purpose is to prevent unfair market practices on the basis of tender procedures, fulfilling the demand for consistency of the legal system through the principle.
Keywords: jednostki samorządu terytorialnego; służby publiczne; prawo finansów publicznych; zasada równości wobec prawa; sąd